FACTUAL REFLECTION OF PANCASILA AS THE BASIS OF THE STATE: UNIFIER AND DEFENSE OF THE INDONESIAN NATION - Ade Arif Firmansyah (Faculty of Law-Universitas Bandar Lampung, 2022)
Pancasila as universal values with a high abstraction nature need to be concretized so that they can live and become the basis for behavior for the people of Indonesia. As the basis of the State for unification and defense from the flow of globalization, Pancasila is actually reflected in the behavior of the government in exercising state power. It is the commitment and attitude of the actions of the symbols of the State that are able to reflect on whether Pancasila can survive as a unifier and defense or not. The discussion shows thatt as the basis of the state, Pancasila is the foundation that unites the diversity of the Indonesian nation in the state, as well as a defense in facing the challenges of world development/globalization. The factual condition of Pancasila as the unifier and defense of the Indonesian nation has been degraded due to the inability of government institutions to realize Pancasila in the life of the state. This degradation can be seen by the emergence of separatist movements that demand to break away from Indonesia, the frequent SARA-related conflicts and the low morality of youth due to the disadvantages of globalization. Therefore, government institutions are obliged and required to be able to realize the values of Pancasila in the life of the nation and state.